The Morphology of Rencong Aceh in the Museum of Aceh - Abdul Manan; Nasruan Hakim; Ahmad Zaki Husaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2019)
As a fascinating weapon, Rencong Aceh cannot be separated from the life of Acehnese people. In order to describe the morphology of which, a qualitative method was implemented to collect the data through observation, interview and document analysis. The collected data were analyzed with descriptive analysis. The four types of Rencong Aceh – rencong meucugek, rencong meukuree, and rencong podoi or puntong – have the structure of Bismillahirrahmanirrahim entirely. Those also possess the letter of Ba. Every morphology form of Rencong Aceh is constant, either in the form of Bismillah, Bismillahirrahmanirrahim, or Ba. Philosophically, the compilation of morphology upon the weapons cannot be disconnected from the Islamic context developed within the social and culture understanding and its practice of the Acehnese people. Every beginning of an action should be initiated with the words of Bismillahirrahmanirrahim. The expression is done to get the mercy and blessing of God, particularly when the enemies attack. Sebagai senjata yang memesona, Rencong Aceh tidak dapat dipisahkan dari kehidupan masyarakat Aceh. Untuk menggambarkan morfologi, metode kualitatif diterapkan untuk mengumpulkan data melalui observasi, wawancara dan analisis dokumen. Data yang terkumpul dianalisis dengan analisis deskriptif. Empat jenis Rencong Aceh - rencong meucugek, rencong meukuree, dan rencong podoi atau puntong - memiliki struktur Bismillahirrahmanirrahim seluruhnya. Mereka juga memiliki surat Ba. Setiap bentuk morfologi Rencong Aceh adalah konstan, baik dalam bentuk Bismillâh, Bismillâhirrahmanirrahim, atau Ba. Secara filosofis, kompilasi morfologi atas senjata tidak dapat dilepaskan dari konteks Islam yang dikembangkan dalam pemahaman sosial dan budaya dan praktiknya terhadap rakyat Aceh. Setiap awal tindakan harus dimulai dengan kata-kata Bismillâhirrahmanirrahim. Ungkapan itu dilakukan untuk mendapatkan rahmat dan berkah Tuhan, terutama saat musuh menyerang.